The Influence of Organizational Culture and Work Involvement on Organizational Commitment Mediated by Job Satisfaction - Haerudin; Lie Liana (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aimed to analyze the influence of organizational culture and work involvement on organizational commitment mediated by job satisfaction. The research used an associative approach with a population of 139 employees of the Demak Regency Regional Health Office. The number of samples is calculated using the Slovin formula so that the number of samples used is 104 employees. Sampling used a purposive sampling technique with the criterion of employee service period of more than 1 year. Data were processed using SPSS software version 23. Data analysis techniques included respondent descriptions, variable descriptions, validity tests, reliability tests, F-tests, R2 tests, t-tests, and Sobel Tests. The results stated that organizational culture has a positive effect on job satisfaction, work involvement has a positive effect on job satisfaction, organizational culture has a positive effect on organizational commitment, work involvement has a positive effect on organizational commitment, and job satisfaction has a positive effect on organizational commitment. Future findings demonstrated that organizational culture has an effect on organizational commitment mediated by job satisfaction, and work involvement has an effect on organizational commitment mediated by job satisfaction.